Pengaruh Penggunaan Learning Management System (LMS) dan Minat Belajar Terhadap Prestasi Belajar Pendidikan Agama Islam Di SMP Islam Al-Azhar 52 Kota Bengkulu - Afifah Fitriana; Edi Ansyah; M Nasron (UIN Fatmawati Sukarno Bengkulu, 2022)
The purpose of this study was to determine the use of learning management system (LMS) affects the learning achievement of Islamic religious education of students of Islamic junior high school Al-Azhar 52 Bengkulu City. Second, learning interest affects the learning achievement of Islamic religious education of students of Islamic junior high school Al-Azhar 52 Bengkulu City. Third, the use of LMS and learning interest affect the learning achievement of Islamic religious education of students of Islamic junior high school Al-Azhar 52 Bengkulu City. The method used in this study is quantitative descriptive approach research, because this study is presented with numbers. The results of this study indicate that First, the use of LMS has an effect of 11.3% on the learning achievement of Islamic religious education of students of Islamic junior high school Al-Azhar 52 Bengkulu City. Second, learning interest has an effect of 20.4% on the learning achievement of Islamic religious education of students of Islamic junior high school Al-Azhar 52 Bengkulu City. Third, there is a significant and positive influence between the influence of LMS usage and learning interest on Islamic religious education learning achievement at Al-Azhar 52 Islamic Junior High School in Bengkulu City with a contribution value of 32.6%.